Designing and Rating Options for Special School Expertise to Support Mainstream Educational Inclusion. Issue 1 (16th December 2019) - Iacono, Teresa; McKinstry, Carol; Wilson, Elena; Bagley, Kerryn; Kenny, Amanda
Abstract: The Victorian Government, Australia, committed to deliver recommendations from a review of the Program for Students with Disabilities. We report on the implementation of Recommendation 7: to explore options for how special schools could become 'centres of expertise' to support inclusion in mainstream schools. Informed by evidence reviews of inclusive education practices and interviews of special and mainstream staff and parents, stakeholders were engaged in a forum to develop a range of options. A larger sample of stakeholders then completed a survey to evaluate them. Forum attendees were parents, education staff, and allied health professionals from special and mainstream schools. They worked in small groups to develop options, which were later grouped into 5 categories. These options were entered into an online survey for distribution to a wider group of stakeholders. Survey respondents were 142 stakeholders from special (71%) and mainstream primary and secondary schools (parents, education staff, and allied health professionals). They rated each option, such that 8 with high ratings for feasibility and acceptability were recommended to support inclusive mainstream education through utilisation of special school expertise. The final list of options focused on collaboration, development, and coordination of networks of special and mainstream schools, and building capacity and leadership to support mainstream schools to meet diverse student need.